Facilitating Trade and Structural Adjustment Experiences in Non-Member Countries - Onodera, Osamu (OECD Trade Policy Papers, 2008)
This paper, together with five other background studies, is a part of a broader research programme addressing trade and structural adjustment issues in non-member economies which was conducted as a follow-up to Trade and Structural Adjustment: Embracing Globalisation (OECD, 2005) which identified policies for successful trade-related structural adjustment. This paper revisits and elaborates on specific parts of these policy recommendations with a view to reassessing their applicability to developing countries. The five background studies; a comparison study comparing East Asia and Latin America and four country case studies (Chile, Ecuador, the Philippines and Thailand), which were conducted as a part of this project, form the basis for the analysis, supplemented by existing literature. The report consists of 4 main sections; The first section provides an introduction and the second section provides an overview of the liberalisation experiences of the four countries. In the third section, some of the ?recommendations in OECD (2005) are revisited with a greater focus on developing countries, covering such issues as i) trade and investment policies, ii) macroeconomic policy, iii) social safety nets and labour market policies, iv) policies to facilitate export response, v) institutional frameworks and regulatory and competition environment, vi) role of multilateral cooperation and regional and bilateral initiatives, and vii) broad based approach to reforms. The fourth section concludes